2002
DOI: 10.1097/00000658-200204000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Human Macrophage Metalloelastase Worsens the Prognosis of Pancreatic Cancer

Abstract: ObjectiveTo evaluate the role of human macrophage metalloelastase (HME) in pancreatic cancer. Summary Background DataHME, a member of the human matrix metalloproteinase family, possesses elastolytic activity and is critical for the degradation of extracellular matrix proteins. Inasmuch as tumor invasion and metastasis formation require lysis of extracellular matrix, HME plays a critical role in both processes. MethodsHME expression was analyzed by Northern blot analysis, reverse transcriptase-polymerase chain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…This circulating elastase is likely to be the inactive proform of pancreatic elastase, which would not thus degrade endostatin. Conversely, pancreatic tumours expressing macrophage metalloelastase have a worse prognosis than those that do not (Balaz et al, 2002). In this instance, we suggest that the elastase is active and degrades endostatin so that angiogenesis can occur as well as promoting invasion.…”
Section: Discussionmentioning
confidence: 78%
“…This circulating elastase is likely to be the inactive proform of pancreatic elastase, which would not thus degrade endostatin. Conversely, pancreatic tumours expressing macrophage metalloelastase have a worse prognosis than those that do not (Balaz et al, 2002). In this instance, we suggest that the elastase is active and degrades endostatin so that angiogenesis can occur as well as promoting invasion.…”
Section: Discussionmentioning
confidence: 78%
“…Two matrix metalloproteinases, MMP7 and MMP12, were among the five marker genes which were newly identified in this study. MMPs are a family of zinc-dependent proteolytic enzymes capable of cleaving extracellular matrix proteins, and the expression of MMPs in cancer tissue has been reported to be associated with the risk of metastasis (32)(33)(34)(35)(36)(37)(38). These two MMPs may play important roles in tumor invasion and the formation of metastasis in gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…167 However, a recent study of patients with pancreatic carcinoma found that overexpression of human macrophage metalloelastase was associated with poorer survival. 168 The enzyme might enhance tumor invasion and metastasis by the degradation of extracellular matrix.…”
Section: Prognostic Significance Of Antiangiogenic Factorsmentioning
confidence: 99%